2018
DOI: 10.1371/journal.ppat.1007334
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of regulatory G-quadruplexes affecting gene expression in human cytomegalovirus

Abstract: G-quadruplex (G4), formed by repetitive guanosine-rich sequences, is known to play various key regulatory roles in cells. Herpesviruses containing a large double-stranded DNA genome show relatively higher density of G4-forming sequences in their genomes compared to human and mouse. However, it remains poorly understood whether all of these sequences form G4 and how they play a role in the virus life cycle. In this study, we performed genome-wide analyses of G4s present in the putative promoter or gene regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 65 publications
1
43
0
Order By: Relevance
“…G-quadruplexes have gained recognition as regulatory nucleic acid structures that influence a number of biological processes. Many members of the Herpesviridae family have been shown to form G-quadruplexes that regulate viral gene expression, viral DNA replication, and virion production (52,53). Moreover, G-quadruplexes have gained recognition as immunomodulatory structures in a few gammaherpesviruses, such as EBV and alcelaphine herpesvirus 1 (AIHV), in which these structures abrogate protein synthesis and restrict antigen presentation, thereby helping in immune evasion (30,54).…”
Section: Discussionmentioning
confidence: 99%
“…G-quadruplexes have gained recognition as regulatory nucleic acid structures that influence a number of biological processes. Many members of the Herpesviridae family have been shown to form G-quadruplexes that regulate viral gene expression, viral DNA replication, and virion production (52,53). Moreover, G-quadruplexes have gained recognition as immunomodulatory structures in a few gammaherpesviruses, such as EBV and alcelaphine herpesvirus 1 (AIHV), in which these structures abrogate protein synthesis and restrict antigen presentation, thereby helping in immune evasion (30,54).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a luciferase reporter system that included different PQSs in viral promoters, NMM was shown to suppress the expression of several mRNAs and to reduce both intracellular and extracellular viral DNA levels. 20 Recently, the anti-CMV activity of a polymerase inhibitor CX-5461, a known G4 ligand currently in phase I clinical trial, was also demonstrated. Interestingly, the compound induced a 2.0 log reduction in viral titer, together with a significant decrease in the amount of viral DNA and pUL44, the viral processivity factor: these data indicate that the effect of CX-5461 is exerted at the viral DNA replication stage of the viral life cycle.…”
Section: Human Cytomegalovirusmentioning
confidence: 99%
“…We also classified pG4s into genic and intergenic PG4s based on General Transfer Format (GTF) format gene annotation of D. melanogaster (Flybase r6. 19) downloaded from Flybase (http://flybase.org/; last access Jan 27, 2018). We used the software bedtools command intersect (27) (v2.25.0) to search pG4s which had at least 1 nt overlap with any protein-coding genes, non-coding genes or psuedogenes and classified them into genic pG4s.…”
Section: The Classification Of Pg4smentioning
confidence: 99%
“…G4s were reported to suppress gene expression (18,19). To test whether the enrichment of intergenic pG4s was responsible for the male-specific fine-tuning of X chromosome in dosage compensation, we then took advantage of RNA-seq data from fly tissues to measure the expression of pG4s.…”
mentioning
confidence: 99%